Comparative Evaluation of Amino Acid Composition of Selected Freshwater and Marine Teleosts - Hitesh U. Shingadia (Journal of Indian Fisheries Association, 2019)
Fishes are the nutritious food commodity for ever hungry human populace with easily digestible protein content rich in amino acids. Amino acid profile of two marine fish species, Mugil cephalus (Linnaeus, 1758); Epinephelus maculatus (Bloch, 1790) and two freshwater fish species, Lates calcarifer (Bloch, 1790); Oreochromis mossambicus (Peters, 1852) purchased from local fish markets in Mumbai was characterized. In the present study only fourteen amino acids were quantified due to limitation of instrumentation facility, of which seven were essential amino acids and seven were non- essential amino acids observed to be present in edible muscle tissue of each of the fish samples. There was significant homogeneity detected in amino acids profiles between marine and freshwater fish species. Amino acids like lysine and leucine were detected significantly (P ≥ 0.05; P ≥ 0.01) in higher percentage, while that of histidine was detected least in both marine and freshwater fishes. Similarly among the non-essential amino acids, glutamic acid and aspartic acids were detected in significantly higher percentage and serine and tyrosine in lower percentage in both marine as well as freshwater fishes. All four fishes showed maximum amount of lysine and glutamic acid. It can be inferred that both marine as well as freshwater fish species studied contains almost all essential and non-essential amino acids that probably amounts for high concentrations of protein and can be acclaimed as a protein rich nutritional supplement because of their easy availability and cultivability will comprehend protein-rich source in magnitudes adequate for sound health of human populace. However need for elaborate characterization further will overcome the limitations in the present findings and substantiate the scope as dietary supplement.